2008
DOI: 10.1111/j.1399-6576.2008.01752.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsed radiofrequency for postherpetic neuralgia

Abstract: PRF lesioning of DRG showed significant pain relief compared with the conventional treatments in patients with intractable PHN. In order to elucidate the mode of action of PRF, further research is needed and the optimal electrical parameters of PRF have to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 9 publications
2
33
0
Order By: Relevance
“…Post-procedure pain scores and tramadol use were decreased, and several health-related quality of life domains were significantly improved through 6 months after treatment in the PRF group compared to the sham group. These results are similar to the reports from open-label studies of a reduction in pain during a 12-week follow up period after PRF treatment of the affected cervical, thoracic, or lumbar DRG in patients with PHN [67]. No complications were encountered in these studies.…”
Section: Peripheral Np Conditionssupporting
confidence: 89%
“…Post-procedure pain scores and tramadol use were decreased, and several health-related quality of life domains were significantly improved through 6 months after treatment in the PRF group compared to the sham group. These results are similar to the reports from open-label studies of a reduction in pain during a 12-week follow up period after PRF treatment of the affected cervical, thoracic, or lumbar DRG in patients with PHN [67]. No complications were encountered in these studies.…”
Section: Peripheral Np Conditionssupporting
confidence: 89%
“…Moreover, DRG radiofrequency lesions seem to perform well without any associated complications; however, the mean follow-up of the studies was only 3.5 months which limited the capacity to detect chronic complications [39, 40]. Our results demonstrate that peripheral nerve stimulation and SCS achieved an average of 76.5 and 64.4% pain reduction; those two procedures are less invasive among neurosurgical options, show promising results and are generally safe.…”
Section: Discussionmentioning
confidence: 72%
“…One study reported a mean reduction of the morphine equivalent dose from 35.2 mg before to 20 mg after the procedure [40]. The study by Kim et al [39] documented that 3/49 (6.1%) patients discontinued all analgesic medication while the rest reduced the dose or maintained it to the pre-procedural levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…117 Pulsed radio-frequency lesioning of the DRG has been assessed in an open case series, and did show some benefit; however, as with most interventions, a study designed to account for the placebo effect is required. 118 Use of lidocaine and methylprednisolone combined (via intrathecal administration) appears to be associated with pain relief in PHN patients, 119 although this has potentially dangerous short-term and long-term adverse effects and the trial has not yet been replicated. 79 Spinal cord stimulation has been used for the treatment of neuropathic pain, and some PHN patients have obtained relief with temporary percutaneous spinal cord stimulation.…”
Section: Interventional Therapiesmentioning
confidence: 99%